2019
DOI: 10.3390/pathogens9010007
|View full text |Cite
|
Sign up to set email alerts
|

Giardiasis Alters Intestinal Fatty Acid Binding Protein (I-FABP) and Plasma Cytokines Levels in Children in Brazil

Abstract: Giardiasis is an intestinal infection caused by ingestion of water or food contaminated with cysts of Giardia lamblia. Susceptibility is higher in children and overall prevalence can reach up to 90% in low-income areas, although outbreaks are also reported in developed countries. Both parasite and immune-mediated epithelial damage has been observed in vitro and in animal models. However, whether enterocytes are directly damaged during infection is not entirely known. Our goal was to identify whether plasma lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
(20 reference statements)
0
7
1
Order By: Relevance
“…However, plasma I-FABP was not elevated in most children, suggesting enterocyte integrity was largely intact ( 62 ). Two studies in preschool children from Bangladesh and Brazil reported higher I-FABP values than in our study ( 63 , 64 ).…”
Section: Discussioncontrasting
confidence: 77%
“…However, plasma I-FABP was not elevated in most children, suggesting enterocyte integrity was largely intact ( 62 ). Two studies in preschool children from Bangladesh and Brazil reported higher I-FABP values than in our study ( 63 , 64 ).…”
Section: Discussioncontrasting
confidence: 77%
“…MrBayes v3.1.2 was used to perform Bayesian analyses with four independent Markov chain runs for 1,000,000 metropolis-coupled MCMC generations, sampling a tree every 100th generation [ 64 ]. References [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ] are cited in the supplementary materials . The first 25% of trees represented burn-in and the remaining trees were used to calculate Bayesian posterior probability.…”
Section: Methodsmentioning
confidence: 99%
“…While the microbiome may modulate immune responses to Giardia , Giardia in turn may initiate and alter immune responses in ways that contribute to dysbiosis, either through direct effects on microbes or by altering the intestinal microenvironment. Giardia has been found to induce Th17 type immune responses, with elevated levels of IL-17 being observed both in mouse models of infection and in Brazilian children infected with Giardia ( Dreesen et al, 2014 ; Dann et al, 2015 ; Cascais-Figueiredo et al, 2019 ; Singer et al, 2019 ). IL-17A is an important mediator of anti-microbial responses and plays a role in the transport of IgA across the epithelium and into the intestinal lumen, where it creates an anti-microbial chemical barrier to protect the underlying epithelium ( Dann et al, 2015 ; Singer et al, 2019 ).…”
Section: Role Of the Microbiome In Giardia Pathogementioning
confidence: 99%